Interparental Conflict and Delinquency Among Chinese Adolescents: Parental Knowledge as a Mediator and Deviant Peer Affiliation as a Moderator - Lu, Hong; Chen, Quanfeng; Xie, Chuyin; Liang, Qiao; Wang, Lanping; Xie, Min; Yu, Chengfu; Wang, Jianping (Frontiers in Psychology, 2020)
Interparental conflict has been found to positively affect adolescent delinquency; however, the underlying mechanism that explains this association remains unclear. This study investigated whether parental knowledge mediates the association between interparental conflict and adolescent delinquency, and whether this mediating process is moderated by deviant peer affiliation. To examine this, a total of 3,129 Chinese adolescents (47.27% boys, Meanage = 14.94 years) completed a survey. Structural equation modeling indicated that the positive association between interparental conflict and adolescent delinquency is mediated by parental knowledge. Moreover, for adolescents with high deviant peer affiliation, interparental conflict was found to positively predict delinquency via parental knowledge; however, this indirect link was nonsignificant for adolescents with low deviant peer affiliation. These findings highlight the influence of parental knowledge and deviant peer affiliation on the association between interparental conflict and adolescent delinquency. This can provide guidance for the development of effective interventions that address the adverse effects of interparental conflict.